Telecommunications submarine cable vulnerability and local performance of firms in developing and transition countries - Joël Cariolle; Maëlan Le Goff; Olivier Santoni (Fondation pour les études et recherches sur le développement international (FERDI), 2019)
We estimate the impact of Internet diffusion on local firm performance in developing and transition economies, by adopting an instrumental variable approach reflecting firm's vulnerability to seismic shocks upon the telecommunications submarine cable (SMC) network. IV within fixed-effect estimations are conducted at the location-level, based on an original sample of some 30,000 firms from 125 locations in around 40 developing and transition countries. Results point to large and positive local impacts of a greater Internet diffusion among firms, induced by lower digital vulnerability, on their average revenue, labour productivity, and employment. These impacts are found to be larger for domestic SMEs, and partly driven by service firms. Moreover, a greater use of Internet is found to increase the number of production workers more than non-production workers in manufactures. This difference seems mostly explained by the large positive effect of internet use on the unskilled production workforce.
Keywords: 330; Internet; digital vulnerabilities; Developing countries; NICT; Submarine cables; infrastructures; telecommunications; firm performance